RENAL FAILURE AND UROLOGICAL ASPECTS - Mo’minov M.Sh (TADQIQOTLAR, 2026)
Abstract: Renal Failure and Urological Aspects Renal failure is a pathological syndrome characterized by a decline in kidney function. It manifests as a sudden and significant reduction or complete cessation of the kidneys’ primary functions—secretory, excretory, and filtration. The disease may occur in two forms: acute renal failure, which develops abruptly, and chronic renal failure, which progresses gradually. This scientific work examines the role of urological factors in the development of renal failure and their significance in treatment strategies. In addition, the social and clinical relevance of the disease and its association with urological disorders are analyzed. Preventive measures aimed at reducing the risk of renal failure are also considered to be of particular importance. These measures include lifestyle modifications, hygienic practices, and pharmacological prevention strategies, all of which are recommended based on scientific evidence.